The association between surgical fixation of hip fractures within 24 hours and mortality: a systematic review and meta-analysis. (1st July 2021) - Welford, Paul; Jones, Conor S.; Davies, Gareth; Kunutsor, Setor K.; Costa, Matt L.; Sayers, Adrian; Whitehouse, Michael R.
Abstract : Aims: The aim of this study was to assess the effect of time to surgical intervention from admission on mortality and morbidity for patients with hip fractures. Methods: MEDLINE and Embase were searched from inception to June 2020. Reference lists were manually assessed to identify additional papers. Primary comparative research studies that recruited patients aged over 60 years, with non-pathological primary proximal femoral fractures that were treated surgically, were included. Studies that did not include a group operated on within 24 hours or which reported time to surgery in calendar days were excluded. Two investigators extracted data on study characteristics, methods, and outcomes. The pre-defined primary outcome was 30-day mortality. Secondary outcomes were complications and mortality at other time points. Relative risks (RRs) with 95% confidence intervals (CIs) were aggregated and were grouped by study-level characteristics. Results: This review included 46 studies (January 1991 to June 2020), comprising 521, 857 hip fractures with 64, 047 postoperative deaths. No randomized controlled trials were eligible for inclusion. In a pooled analysis of 15 studies, RR of mortality at 30 days comparing time to surgery < 24 hours with > 24 hours was 0.86 (95% CI 0.82 to 0.91; I 2 = 69%; 95% CI 50% to 81%; p-value for heterogeneity < 0.001). The association was stronger in observational studies that did not adjust for confounders than in those that adjusted for multiple covariates. In a pooled analysis of six studies, the RR of mortality at 30 days comparing time to surgery < 24 hours with 24 to 36 hours was 0.87 (95% CI 0.81 to 0.93; I 2 = 65%; 95% CI 16% to 85%; p-value for heterogeneity = 0.014). Conclusion: This meta-analysis indicates reduced mortality for patients operated within 24 hours compared with those operated on beyond 24 hours or within 24 to 36 hours. Where resources allow and there is no specific reversible contraindication to early surgery, we recommend that hip fractures should be surgically treated within 24 hours. Cite this article: Bone Joint J  2021;103-B(7):1176–1186.